1995
DOI: 10.1099/00222615-43-3-161
|View full text |Cite
|
Sign up to set email alerts
|

Adherence characteristics of coagulase-negative staphylococci isolated from patients with infective endocarditis

Abstract: Summary. Coagulase-negative staphylococci isolated from patients with endocarditis were divided according to whether the infection was of native or of prosthetic valves and was acquired either in the community or in hospital. Comparisons were made with strains from intravenous line-associated bacteraemias. All strains were examined by direct and indirect adherence tests. Line-associated bacteraemia strains were more likely to produce slime and were more hydrophilic but were less likely to attach HEp2 tissue cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Discrepancy between these two methods was low and in accordance with the results of other authors (Freeman et al , 1989; Cree et al , 1995). CRA and Christhensen methods are qualitative and not 100% reliable since Christhensen method shows low success for detection of weak slime production (Christensen et al , 1982) and results obtained from CRA method can often be misinterpreted due to variation in black pigmentation of colonies or decrease of the black color with the time (Freeman et al , 1989; Mariana et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Discrepancy between these two methods was low and in accordance with the results of other authors (Freeman et al , 1989; Cree et al , 1995). CRA and Christhensen methods are qualitative and not 100% reliable since Christhensen method shows low success for detection of weak slime production (Christensen et al , 1982) and results obtained from CRA method can often be misinterpreted due to variation in black pigmentation of colonies or decrease of the black color with the time (Freeman et al , 1989; Mariana et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Plates were incubated on 35 °C in aerobic conditions for 24 h after which results were interpreted according to following criteria: black colonies with dry crystalline consistency indicated for the positive result (slime production), pink colonies were usually present at non-slime producers and darkening of the colonies with the absence of the dry-crystalline morphology was categorized as indeterminate result (Freeman et al , 1989: Cree et al , 1995). …”
Section: Methodsmentioning
confidence: 99%
“…Second, although biofilm production per se cannot be used to decide on the need to treat S. epidermidis bacteraemias, differences were found between patients infected by isolates either producing or failing to produce biofilm. Several studies have attempted to evaluate the role of biofilm production in virulence, but the results have been somewhat contradictory [17][18][19][20]. However, recent clinical studies have suggested that PIA is important for biofilm accumulation, and that the presence of the icaADBC operon coding for PIA is related to the clinical significance of S. epidermidis isolates [4][5][6][7][8][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Glycocalix promotes intercellular adhesion, captures nutrients, and protects microorganisms from the deleterious effects of antimicrobial agents. Many investigators consider slime a virulence factor, because strains of CNS from prosthetic valve endocarditis are more likely to produce it than are those not cultured at University of Nebraka-Lincoln Libraries on April 4, 2015 http://cid.oxfordjournals.org/ Downloaded from from such infections [26]. Christensen et al [27] clearly showed that slime-producing CNS are more likely to be isolated from a device than from random blood cultures.…”
Section: Pathogenesis Of Odrismentioning
confidence: 98%